Quem decide? Formaç\~ao da agenda e formulaç\~ao de políticas no executivo federal - Felix Lopez; Jacqueline Borges; Noëlle Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– In this work, we will analyze the routines and protocols, as well as the agents and the organizations, that are decisive in the agenda-setting and in the formulation of government policies at the Executive Branch. The analysis is based on two cases: the Ministry of National Integration (MI) and the Ministry of Social Development (MDS). We use documents and data collected in 28 semi-directive interviews with members of top-level positions in each Ministry and in the Presidency of the Republic. We argue that the agenda-setting is divided into two parts: the President's priority agenda and ministers' agenda. However, the policy formulation - including the priority - almost always takes place at the ministerial level. The bureaucracy of experts is indispensable to formulate any policy but acts through political delegation, not by their own. Ministers play a pivotal role in setting the agenda, but the ideological intra-coalition conflict - manifested by parties with heterogeneous preferences - is no obstacle to the President, who can push ahead with the agenda of his interest.
Keywords: H1; H19; 330; federal Executive Branch; Presidency of the Republic; coalitional presidentialism; public policy; government process in Brazil